Protective Effect of Fenofibrate on Oxidative Stress-Induced Apoptosis in Retinal-Choroidal Vascular Endothelial Cells: Implication for Diabetic Retinopathy Treatment - Ying-Jung Hsu; Chao-Wen Lin; Sheng-Li Cho; Wei-Shiung Yang; Chung-May Yang; Chang-Hao Yang (MDPI AG, 2020)
Diabetic retinopathy (DR) is an important microvascular complication of diabetes and one of the leading causes of blindness in developed countries. Two large clinical studies showed that fenofibrate, a peroxisome proliferator-activated receptor type α (PPAR-α) agonist, reduces DR progression. We evaluated the protective effects of fenofibrate on retinal/choroidal vascular endothelial cells under oxidative stress and investigated the underlying mechanisms using RF/6A cells as the model system and paraquat (PQ) to induce oxidative stress. Pretreatment with fenofibrate suppressed reactive oxygen species (ROS) production, decreased cellular apoptosis, diminished the changes in the mitochondrial membrane potential, increased the mRNA levels of peroxiredoxin (Prx), thioredoxins (Trxs), B-cell lymphoma 2 (Bcl-2), and Bcl-xl, and reduced the level of B-cell lymphoma 2-associated X protein (Bax) in PQ-stimulated RF/6A cells. Western blot analysis revealed that fenofibrate repressed apoptosis through cytosolic and mitochondrial apoptosis signal-regulated kinase-1 (Ask)-Trx-related signaling pathways, including c-Jun amino-terminal kinase (JNK) phosphorylation, cytochrome c release, caspase 3 activation, and poly (ADP-ribose) polymerase-1 (PARP-1) cleavage. These protective effects of fenofibrate on RF/6A cells may be attributable to its anti-oxidative ability. Our research suggests that fenofibrate could serve as an effective adjunct therapy for ocular oxidative stress-related disorders, such as DR.